Academic social networking sites for researchers in Central Universities of Delhi: A study of ResearchGate and Academia. Issue 1 (7th February 2018) - Asmi, Nowsheeba Ashraf; Margam, Madhusudhan
Abstract : Purpose: This paper aims to explore the usage of academic social networking sites (ASNSs) among the research scholars in Central Universities of Delhi, India. Design/methodology/approach: A structured questionnaire was designed and personally distributed among 200 research scholars in Central Universities in Delhi in May 2016. Of this, 180 filled-in questionnaires were personally collected by the investigator, eliciting a response rate of 90 per cent. Findings: Findings of the study reveals that research scholars have knowledge of ASNSs. ResearchGate and Academia are the most used ASNSs among research scholars. ResearchGate is used the most for connecting to other research scholars, and Academia is used for sharing and following research. Additionally, ASNSs help research scholars in research and learning and to share research ideas and experience. Finally, research scholars find ASNSs time-consuming and have cited data security as main concern for using academic social networks. Research limitations/implications: The findings of the study show that potential uses of ASNSs in Indian libraries are slow compared to the libraries of developed countries and some of the developing countries. It is suggested that universities under study may realize the benefits of ASNSs and incorporate these tools in their websites to enhance faster transfer and retrieval of information. Practical implications: The results also stress upon the responsibility of research supervisors to accord knowledge of ASNSs among research scholars and encourage them to join and use ASNSs efficiently and effectively for building professional connections and collaborations in their research area. Social implications: The study is significant because it represents one of the earliest works to shed the light on the current level of use of SNSs and ASNSs by research scholars in Central Universities in Delhi, which are in primitive nature. They provide space for self-expression, research updates, expert advice, connecting with fellow scholars, creating and joining events and discussions, presenting their views on a particular topic, finding collaboration on projects, finding jobs and much more. Originality/value: ASNSs have further promoted the open source movement. The paper apprises the academic stakeholders about the unique features, adoption, acceptability and usage of ASNSs for research work, exchange of information and collaborations, so that more productive and quality research is produced. The findings will also guide research scholars to find popular ASNSs, so that they can build more academic connections.